PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA KELAS IIC SDN 91 PEKANBARU - Ermawati '; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study is based on the lowly of the result of social subject in grade 2nd of SDN 91 Pekanbaru year 2014/2015 which is only 12 students (40%) from 30 students within minimal completeness criterion states is 62. This research is classroom action research. The purpose of this research is to improve the quality of learning process and IPS learning outcomes of 2C grade students of SDN 91 Pekanbaru trough the implementation of direct learning model. Research carried out in January until June of the academic year 2014/2015. The subject of this research is class IIC. The instruments used in this study is the teacher and student activity sheets as well as learning about the test result. This research data analyzed using descriptive analysis. This study present that the application of direct learning model can improve student learning outcomes it can be seen from the results of daily tests in the first cycle at 69.17 and on the second cycle of 78.37. The teacher activity is not good at the beginning, but then at the second cycle with good criteria and then with very well criteria. The students activity in the first cycle obtained an average of 60%, the second cycle an average of 60% with good category. Direct instructional model can be applied to improve student learning outcomes.Keywords: Learning Models Direct, IPS learning outcomes